MODEL GAGNE’S NINE EVENTS OF INSTRUCTION DALAM PEMBELAJARAN DI SEKOLAH DASAR: TINJAUAN LITERATUR - Yuli Puji Lestari; Sri Marmoah (PT. Hasba Edukasi Mandiri, 2025)
This study aimed to analyze the relevance and adaptation of Gagné’s Nine Events of Instruction in elementary school learning, particularly in the implementation of the Merdeka Curriculum. The method employed was a literature review of scholarly articles published between 2020 and 2025. The findings indicate that Gagné’s model offers advantages through its systematic instructional structure, enhancing student engagement and learning motivation, and is highly applicable at the elementary level. However, its application requires flexibility, especially in addressing the challenges of project-based learning and digital technology integration. The study concludes that adapting Gagné’s model is essential to align with the principles of the Merdeka Curriculum, particularly in strengthening character, literacy, and 21st-century skills.